STUDI PENGEMBANGAN STANDAR ERGONOMI DESAIN MEDIA SIGNAGE PADA UNIVERSITAS TELKOM - Anggraini Agnesia (Ide dan Dialog Desain Indonesia (Idealog), 2024)
Abstract : Signage is one of the important elements in the information field that forms the image of an environment. In a college environment, signage is one of the supporting factors for architectural elements that function to direct someone in finding and finding the location or facility they want to go to. Telkom University is a tertiary institution with adequate facilities however, the existing signage at Telkom University still does not meet the existing ergonomic standards. If the ergonomics problem is left alone, there will be an impact that is not good for Telkom University. The purpose of this study is to find out how good signage dimensions are used by Telkom University in accordance with existing standards. To find out this research uses qualitative methods. Qualitative research methods carried out by means of observation, field studies and supplemented with additional data from Telkom University student questionnaires. Based on the results of the data processing obtained, the authors make a recommendation for a good signage design to be used at Telkom University. Keywords : Signage, college, ergonomic